Perceptions of Patients and Officers towards the Use of Online and Offline Registration Systems at the Surgical Polyclinic of Gatot Soebroto Army Central Hospital - Darmawan, Rifqi Helmi; Adi Widodo; Daniel Happy Putra; Noor Yulia (HM Publisher, 2022)
In this era of digital technology, development makes it easier for humans to do things such as seek treatment easily and practically. Registration application online still has drawbacks, namely bugs in the application, the queue paper printing machine does not work, and error system barcode. Online and offline registration. Descriptive method using quantitative analysis. This research was conducted at Gatot Soebroto Army Central Hospital with a sample of 45 offline and 45 online, and 7 registration officers. SOP only covers offline, for SOP online still does not exist. Most of the patients in offline and online registration stated that the quality of service, knowledge, experience, and satisfaction was good. Officers feel that there has been a change since the online registration because it has become a new thing in the surgical polyclinic because the officer at registration at the surgical polyclinic assumes that it is necessary to socialize with patients on the online application because the majority of patients do not register online because they do not know how to register online, especially patients Elderly officers are of the opinion that online registration makes it easier at the registration section.